2005
DOI: 10.1021/jf051721q
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of the Olive Oil Phenols Hydroxytyrosol, Tyrosol, and Hydroxytyrosyl Acetate by Human Hepatoma HepG2 Cells

Abstract: To study the potential hepatic metabolism of olive oil phenols, human hepatoma HepG2 cells were incubated for 2 and 18 h with hydroxytyrosol, tyrosol, and hydroxytyrosyl acetate, three phenolic constituents of olive oil. After incubation, culture media and cell lysates were hydrolyzed with β-glucuronidase and sulfatase and analyzed by LC-MS. In vitro methylation, glucuronidation, and sulfation of pure phenols were also performed. Methylated and glucuronidated forms of hydroxytyrosol were detected at 18 h of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
81
1
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 80 publications
(89 citation statements)
references
References 28 publications
6
81
1
1
Order By: Relevance
“…To study the potential hepatic metabolism of olive oil phenols, human hepatoma HepG2 cells were incubated for 2 and 18 h with Ty, Hyty and Hyty acetate (Mateos et al, 2005 glucurono-and methyl-, but no sulfo-conjugates, were found. Olive oil phenols are metabolized by the liver as well, as suggested by these results.…”
Section: Absorption and Dispositionmentioning
confidence: 99%
“…To study the potential hepatic metabolism of olive oil phenols, human hepatoma HepG2 cells were incubated for 2 and 18 h with Ty, Hyty and Hyty acetate (Mateos et al, 2005 glucurono-and methyl-, but no sulfo-conjugates, were found. Olive oil phenols are metabolized by the liver as well, as suggested by these results.…”
Section: Absorption and Dispositionmentioning
confidence: 99%
“…Human hepatoma cell line (HepG2) is widely used for biochemical and nutritional studies as a cell culture-based model of human hepatocytes since they retain their morphology and most of their biological functions in vitro. [9] Cell culture studies conducted previously have confirmed that diverse flavonoids, [10] olive oil phenols [11] and phenolics from juices [12] are readily absorbed and metabolized by cultured HepG2 cells.…”
Section: Introductionmentioning
confidence: 75%
“…Such a chemical modification has been previously demonstrated to improve its permeability [22] , while still maintaining the biological activity of the parent compound; this is probably owed to the extensive deacetylation by carboxylesterases. Deacetylation can take place either within the cell, upon absorption of the acetylated molecule, or in the extracellular space created by the secreted esterases [26] . In addition, Procopio et al [22] have demonstrated the increased anti-inflammatory activity of Ac-OLE as compared to OLE both in vitro as a COX-1 and COX-2 inhibitor, and also in vivo as a protecting agent against the carrageenan-induced paw edema in mice.…”
Section: Discussionmentioning
confidence: 99%